miR-362-3p suppresses ovarian cancer by inhibiting LRP8 - Chun Li (Elsevier, 2022)
Background: Ovarian cancer is one of the most common female cancers, with a high incidence worldwide. Aberrant expression of low‐density lipoprotein (LDL) receptor‐related protein 8 (LRP8) and microRNA (miR)-362-3p is involved in the pathogenesis of different cancers. Methods: We aimed to elucidate the underlying mechanism of the miR-362-3p-LRP8 axis in ovarian cancer. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used to examine miR-362-3p and LRP8 expression in ovarian cancer tissues and cells. The luciferase assay was used to determine the relationship between miR-362-3p and LRP8. The function of overexpression of miR-362-3p and LRP8 was determined by assessing the cell viability using the cell counting kit 8 (CCK-8) assay, proliferation using 5′‑bromo-2′-deoxyuridine (BrdU) assay, migration using wound healing assay, invasion using transwell assay, and the protein expression levels of matrix metalloproteinase (MMP)-2, MMP9, and integrin α5 or β1 using western blotting assays in ovarian cancer cells. Results: miR-362-3p expression levels were decreased in ovarian cancer tissues and cells and negatively correlated with LRP8 levels. Overexpression of miR-362-3p dramatically repressed cell growth. Furthermore, overexpression of LRP8 significantly facilitated the proliferation, migration, and invasion of ovarian cancer cells, which counteracted the inhibitory effect of miR-362-3p on ovarian cancer cell growth. Conclusions: We reported that miR-362-3p hampered cell growth by repressing LRP8 expression in ovarian cancer cells. Our results provide new insights into ovarian cancer, involving both miR-362-3p and LRP8, which can be used as potential biomarkers for the treatment of ovarian cancer.